Perovskite CaZrO3 for efficient ozonation treatment of organic pollutants in wastewater. Issue 11 (15th March 2021) - Han, Peiwei; Lv, Hongxia; Li, Xiaogang; Wang, Shengzhe; Wu, Zhilian; Li, Xiangnan; Mu, Zhao; Li, Xinjun; Sun, Chenglin; Wei, Huangzhao; Ma, Lei
Abstract : The presence of oxygen vacancy on the surface of CaZrO3 accelerates the decomposition of ozone and generates reactive oxygen substances to act on the mineralization of m -cresol. Abstract : Catalytic ozonation with nano-perovskite oxides is a more efficient and advanced oxidation process for the mineralization of organic pollutants. In this study, by regulating the amount of polyethylene glycol during the synthesis of CaZrO3 perovskite-type oxides by the co-precipitation method, efficient surface oxygen vacancies were formed in CaZrO3 . Owing to the presence of abundant oxygen vacancies, CaZrO3 modified by PEG exhibited a much higher catalytic activity than unmodified CaZrO3 . It was further discovered from the EPR results that the main active oxygen species depend on the surface structure of CaZrO3 . The variation of oxygen vacancies on the surface of the catalyst with PEG addition stimulated ozone decomposition to generate a large number of superoxide radicals. This study not only proposed a method to improve the activity of the catalyst, but also further studied the reaction mechanism of CaZrO3 catalyzed ozonation. It provides a solid theoretical basis for the industrial application of catalytic ozonation technology.